A protein–miRNA biomic analysis approach to explore neuroprotective potential of nobiletin in human neural progenitor cells (hNPCs) - Jahan, Sadaf; Ansari, Uzair Ahmad; Srivastava, Ankur Kumar; Aldosari, Sahar; Alabdallat, Nessrin Ghazi; Siddiqui, Arif Jamal; Khan, Andleeb; Albadrani, Hind Muteb; Sarkar, Sana; Khan, Bushra; Adnan, Mohd; Pant, Aditya Bhushan (Frontiers in Pharmacology, 2024)
Chemical-induced neurotoxicity is increasingly recognized to accelerate the development of neurodegenerative disorders (NDs), which pose an increasing health burden to society. Attempts are being made to develop drugs that can cross the blood-brain barrier and have minimal or no side effects. Nobiletin (NOB), a polymethoxylated flavonoid with anti-oxidative and anti-inflammatory effects, has been demonstrated to be a promising compound to treat a variety of NDs. Here, we investigated the potential role of NOB in sodium arsenate (NA) induced deregulated miRNAs and target proteins in human neural progenitor cells (hNPCs). The proteomic and micro-RNA (miRNA) profiling was done for different groups, i.e., unexposed control, NA exposed, NA+NOB, and NOB. Following the correlation analysis between deregulated miRNAs and target proteins, the validation studies were conducted for selected genes by RT-PCR analysis. The proteomic analysis showed significantly deregulated proteins associated with neurodegeneration pathways, response to oxidative stress, RNA processing, DNA repair, and apoptotic process following exposure to NA. The Open Array analysis confirmed that NA exposure significantly altered the miRNAs that regulate P53 signalling, Wnt signalling, Cell death, and Cell cycle pathways. The Real Time-PCR validation studies concur with proteomic data as marker genes associated with autophagy and apoptosis (HO-1, SQSTM1, LC-3, Cas3, Apaf1, HSP70, and SNCA1) were altered following exposure to NA. It was observed that the treatment of NOB significantly restored the deregulated miRNAs and proteins toward the basal levels. Hence, it may be considered as one of its neuroprotective mechanisms. Together, the findings are promising to demonstrate the potential applicability of NOB as a neuroprotectant against chemicalinduced neurotoxicity.